Decreasing the undernotification of anaphylaxis deaths in Brazil through the International Classification of Diseases (ICD)‐11 revision. Issue 1 (1st September 2016) - Tanno, L. K.; Bierrenbach, A. L.; Calderon, M. A.; Sheikh, A.; Simons, F. E. R.; Demoly, P.; ,
Abstract: Background: In 2012, an analysis of the Brazilian mortality database demonstrated undernotification of anaphylaxis deaths due, at least in part, to difficult coding under the International Classification of Diseases (ICD)‐10. This work triggered a cascade of strategic international actions supported by the Joint Allergy Academies and the ICD World Health Organization (WHO) representatives to update the classifications of allergic disorders for the ICD‐11 revision. These efforts have resulted in the construction of the new 'Allergic and hypersensitivity conditions' section under the 'Disorders of the Immune system' chapter. Objective: To analyze the capacity of the new ICD‐11 revision to capture anaphylaxis deaths. Methods: We re‐estimated the anaphylaxis deaths that occurred in Brazil during the period 2008 to 2010, utilizing this new framework and the database of the Brazilian mortality information system that had initially been extracted in May 2011. However, in 2016, a manual review of each of the 3638 records was performed. Results: We identified 639 anaphylaxis deaths, of which 95% were classified as 'definitive anaphylaxis deaths'. In contrast to the 2012 published data, we found a higher number of cases; moreover, all 606 definitive anaphylaxis deaths would be considered as underlying causes of death utilizing the ICD‐11 revision. Conclusion: This study is the first example of how the new 'Allergic and hypersensitivity conditions' section of the forthcoming ICD‐11 can improve the quality of official vital statistics data and the visibility of an important public health concern. This research will facilitate comprehensive, comparable population‐based epidemiologic data collection on anaphylaxis.